Optimization of thermoplastic pultrusion - Chew, Kevin Soon Poo. (2008)
In this dissertation, the optimization of initial process and primary conditions such as heating of composite and cooling of die for thermoplastic composite pultrusion will be discussed. The simulation algorithm for the optimization process will be based on three- dimensional Finite Element / Nodal Control Volume (FE / NCV) procedure previously developed for optimization of thermosetting composites. In this project, the similar optimization procedure will be developed to suit the optimization of thermoplastic composite.